An electrochemical sensor based on hierarchical nickel oxide nanostructures doped with indium ions for voltammetric simultaneous determination of sunset yellow and tartrazine colorants in soft drink powders. Issue 21 (13th May 2021) - Moarefdoust, Mohammad Mehdi; Jahani, Shohreh; Moradalizadeh, Mehran; Motaghi, Mohammad Mehdi; Foroughi, Mohammad Mehdi
Abstract : Electrochemical sensor based on 3D raspberry-like In 3+ /NiO hierarchical nano-structure modified glassy carbon electrode for simultaneous detecting of sunset yellow and tartrazine was fabricated. Abstract : The current study was designed to develop a single-step and simple approach to effectively fabricate three-dimensional raspberry-like In 3+ /NiO hierarchical nanostructures (In 3+ /NiO RLHNSs) as a modifier, which was subsequently characterized by the techniques of X-ray diffraction (XRD), energy dispersive spectrometry (EDS) and field emission scanning electron microscopy (FE-SEM). The new prepared nano-modifier was practically used to co-detect electrochemically sunset yellow and tartrazine dyes. Potent sensitivity and acceptable selectivity were obtained for the produced In 3+ /NiO RLHNSs to co-detect both the food colorants, thus providing oxidation peaks in differential pulse voltammetry (DPV) with a peak potential separation of ca. 190 mV. The results showed a 5.14-fold and 8.07-fold increase in the electrochemical response of our modified electrode to sunset yellow and tartrazine, respectively, compared to the control (the unmodified electrode). Limits of detection of 2.7 and 3.1 nM were calculated for sunset yellow and tartrazine, respectively. The results from the interaction of common food additives showed satisfactory outcomes for the application of this method in determining sunset yellow and tartrazine in several beverage specimens. Other useful documentation was obtained for the production of portable food additive sensors.